Ratio Effect of Breadfruit Flour and Wheat Flour on Cookies Characteristics - Hendrawan Hendrawan; Alti Martia; Raihanita Nurul Jannah (International Journal of Quantitative Research and Modeling, 2023)
Cookies are dried and sweet food products made from wheat flour, fat, and sugar baked with dried texture and less than 5% moisture content. The flour used in this study was substituted by breadfruit flour as an attempt to reduce the amount of wheat flour consumption also utilizes native crops. The purpose of the study was to determine the right ratio of breadfruit flour and wheat flour to get the best characteristics of cookies. The study was done at Food Processing Lab and Chemistry Lab of Ma’soem University which was conducted in 2022 on September to October. The method used in this study was Randomized Block Design (RBD) with 5 repetitions and 5 treatments. The criteria tested were organoleptic (color, aroma, texture, flavour), chemical properties (water content, carbohydrate content, calories value of cookies). The result indicated that ratio between breadfruit flour and wheat flour effected the water content, carbohydrate content, calories, aroma, texture, and flavor of cookies. The best characteristic of cookies made from treatment C (45:55) based on water content and carbohydrate content.